If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(1/3+2x)=-2(x-4)
We simplify the equation to the form, which is simple to understand
-6(1/3+2x)=-2(x-4)
Simplifying:
-6*( + 0.333333333333+2x)=-2*(x-4)
Reorder the terms in parentheses
+(-2-12x)=-2*(x-4)
Remove unnecessary parentheses
-2-12x=-2+*(+x-4+)
Reorder the terms in parentheses
-2-12x=+(-2x+8)
Remove unnecessary parentheses
-2-12x=-2x+8
We move all terms containing x to the left and all other terms to the right.
-12x+2x=+8+2
We simplify left and right side of the equation.
-10x=+10
We divide both sides of the equation by -10 to get x.
x=-1
| 3x-8x=20 | | -3=y-4 | | (7wz^4)(5w^5z^3)= | | 6x^2+6y^2=150 | | 10+12x+29=180 | | 3(4x+1)=x | | -2-3k=1 | | -15(-18x+21)=9(-3x+229) | | -40=-24t | | 5(a-2)+15=45 | | -15(-18x+21)=(-3x+229) | | 64x+30y=180 | | 24*8= | | i^8= | | h=20-16t^2+32t | | Y=2x^2+8x | | 5/4a+1/2=7/9 | | -6+3n=-7(n+8) | | 5x-4=12-2x | | 10d=200 | | X+0.6y=88 | | 6n-28=-30+4n | | -6+3n=-7 | | 4x+2=6+4x | | 10+d=200 | | -27=6y | | 6y+5=2y+7 | | 25n^2-20n=1 | | 10x-4=11+9x | | -6=z/4 | | x-0.7=8.86 | | 4x-(9-3x)=8x-men |